PHYSIOLOGICAL ACTIVITY ANALYSIS AND GROWTH OF EBONY SEEDLINGS (Diospyros celebica Bakh) TREATED BY VARIOUS BIOFERTILIZER COMBINATIONS - Larekeng, Siti Halimah; Lamanda, Sukriati A.; Restu, Muh. (Association of Indonesian Forestry and Environment Researchers and Technicians, 2024)
Ebony is one of slow-growing spe- cies), that of suspected to be the triggering factors to prone to extinction. In addition, the nature of ebony seeds is recalcitrant, so they cannot be stored for a long time. Other factors affecting seed germination are the degree of maturity, size, and weight of the seeds. Seeds harvested before the physiological maturity level would not have high viability and even could not germinate well due to the in-sufficient of food reserves, and un-perfect embryo formatio. Bio-fertilizer is used to help accelerate the growth of ebony. This study aims to analyze the combination of bio fertilizers which would be giving a better effect on the physiological activity and growth of ebony seedlings. Morphological and physiological variables measurement were used in this study. The research design used a Completely Randomized Design at a real level of 5%. If the fingerprint results obtained have a real effect, then a further test of the Duncan Multiple Range Test is carried out. Re- search results showed that seed coating treatment of 45% Penicillium microbial solution + seed coating) gave the best results in each variable of both growth and physiology of ebony seedlings, while in the treatment without seed coating, Sargassum microbial solution 30% indicates good results in each variable of growth and physiology of ebony seedlings. Treatment with the immersion of seeds in microbes can produce a high percentage in each variable.